2015
DOI: 10.7150/thno.13048
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inflammation in an Acute on Chronic Model of Inflammatory Bowel Disease with Ultrasound Molecular Imaging

Abstract: Background: Ultrasound (US) molecular imaging has shown promise in assessing inflammation in preclinical, murine models of inflammatory bowel disease. These models, however, initiated acute inflammation on previously normal colons, in contrast to patients where acute exacerbations are often in chronically inflamed regions. In this study, we explored the potential of dual P- and E-selectin targeted US imaging for assessing acute inflammation on a murine quiescent chronic inflammatory background.Methods: Chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…7 Additionally, given the clarity of the colon wall images obtained, this technique may prove useful in mouse models of colitis and inflammatory bowel disease. 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…7 Additionally, given the clarity of the colon wall images obtained, this technique may prove useful in mouse models of colitis and inflammatory bowel disease. 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Several potential applications of ultrasound molecular imaging exist. Molecular imaging of tumor endothelial markers may help better discriminate between benign and malignant disease [3,4]. After tumor treatment, molecular imaging may provide early indication of tumor response, as molecular changes may precede changes in tumor volume [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…US molecular imaging combines the advantages of US with those of molecular imaging by using molecularly targeted contrast agent microbubbles and has been recently translated to first-in-human clinical trials in cancer imaging (20,21). By targeting binding ligands to the microbubble shell that recognize inflammation markers that are overexpressed in patients with IBD such as P-selectin and Eselectin (22)(23)(24)(25), US molecular imaging allows quantitative assessment of inflammation in IBD at the molecular level at various anatomic sites after a single injection of molecularly targeted contrast agent (23)(24)(25)(26). Proof-of-principle studies have shown the feasibility of dual P-and E-selectin-targeted US molecular imaging for assessment of inflammation and excellent correlation with other molecular imaging techniques such as PET and histologic examination and immunofluorescence as reference standards in various rodent models of acute and acute-on-chronic IBD (24,25).…”
mentioning
confidence: 99%